DEVELOPMENT OF INDUSTRIES AND MANUFACTURING INFRASTRUCTURE AFTER THE OCTOBER REVOLUTION: HISTORICAL ASPECT AND PERSPECTIVES OF FORMATION - Gasanov, Magomed Alievic (History, Archeology and Ethnography of the Caucasus, 2018)
The paper analyzes the historical aspects of the development of industrial infrastructure after the October Revolution and the prospects for the integrated formation of an infrastructure subsystem. Taking into account the data of archival materials, the role and importance of the branch in the socio-economic development of the republic are explored. At the same time, in the opinion of the author, an important role belongs to the technical re-equipment and increasing the efficiency of all sub-sectors of the production infrastructure. It is noted that the practical use of the results of the analysis will help accelerate market transformations in the areas of the region’s production and transport infrastructure. It describes the growth of agricultural production, the developing freight turnover of the cooperative sector, the need for urgent delivery of raw materials for the canning industry, construction of a power station in the mountains. The needs of trade necessitated the rapid development of industrial infrastructure. The period after the October Revolution marked the beginning of the construction of the road network and the penetration of machines into the mountains for servicing freight, postal and passenger traffic. The analysis allows us to draw conclusions that must be taken into account when building an effective system for managing the production infrastructure at the present stage of development. The enormous importance of the production infrastructure is determined by the fact that the economy of the country and its regions is a single national economic complex. It is noted that the formulated scientific and practical recommendations and proposals aimed at improving the efficiency and effective operation of industrial infrastructure sectors, taking into account the use of the geo-sectoral resource. The results presented in the study can be used in the concept of socio-economic development of the industrial infrastructure of the region. In this regard, the search for management reserves and deepening the efficiency of the development of the industrial infrastructure of the region in the context of innovative economic transformations are of special interest for science, and also of practical importance.